Transcriptome Analysis of Trichothecene-Induced Gene Expression in Barley - Jayanand Boddu; Seungho Cho; Gary J. Muehlbauer (Molecular Plant-Microbe Interactions, 2007)
Fusarium head blight, caused primarily by Fusarium graminearum, is a major disease problem on barley (Hordeum vulgare L.). Trichothecene mycotoxins produced by the fungus during infection increase the aggressiveness of the fungus and promote infection in wheat (Triticum aestivum L.). Loss-of-function mutations in the TRI5 gene in F. graminearum result in the inability to synthesize trichothecenes and in reduced virulence on wheat. We examined the impact of pathogen-derived trichothecenes on virulence and the transcriptional differences in barley spikes infected with a trichothecene-producing wild-type strain and a loss-of-function tri5 trichothecene nonproducing mutant. Disease severity, fungal biomass, and floret necrosis and bleaching were reduced in spikes inoculated with the tri5 mutant strain compared with the wild-type strain, indicating that the inability to synthesize trichothecenes results in reduced virulence in barley. We detected 63 transcripts that were induced during trichothecene accumulation, including genes encoding putative trichothecene detoxification and transport proteins, ubiquitination-related proteins, programmed cell death-related proteins, transcription factors, and cytochrome P450s. We also detected 414 gene transcripts that were designated as basal defense response genes largely independent of trichothecene accumulation. Our results show that barley exhibits a specific response to trichothecene accumulation that can be separated from the basal defense response. We propose that barley responds to trichothecene accumulation by inducing at least two general responses. One response is the induction of genes encoding trichothecene detoxification and transport activities that may reduce the impact of trichothecenes. The other response is to induce genes encoding proteins associated with ubiquitination and cell death which may promote successful establishment of the disease.